Kebijakan Pemerintah Daerah dalam Perubahan Data Akta Kelahiran di Disdukcapil Kabupaten Karanganyar - Abdullah Faqih Ashiddiqy (Universitas Sebelas Maret, 2021)
This study aims to find out the main causes of birth certificate data changes in the Population and Civil Registration Office of Karanganyar Regency, to know the policies of the Karanganyar District Government in the settlement of cases of changes in birth certificate data, and to know the inhibitory factors and supporting local government policies in resolving cases of changes in birth certificate data in Karanganyar Regency.In this study used an empirical juridical approach. With data collection techniques through observation, interview, and documentation studies. The results showed that the main cause of the name change case as in the Court Determination No. 2/Pdt.P/2021/PN Krg name change on the birth certificate was done because the applicant is better known in his residential environment as Antok Saryanto than Saryanto.Then in the case of correcting the name of the parent on the birth certificate in the name of Esti Rahayu the correction was done because there was an error in writing the name of the parent, Sumarsih should be Sunarsih as written on the Family Card and the parent's Marriage Certificate. Karanganyar District Government Policy in resolving cases of changes in birth certificate data in accordance with the provisions in the legislation The inhibitory factors of this policy are cultural factors and community factors. Supporting factors are legal factors, law enforcement factors, and facilities or facilities factors.